2003
DOI: 10.1046/j.1526-4610.2003.03005.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Factors in Migraine: A Population‐Based Study of Women Aged 40 to 74 Years

Abstract: Although many women with migraine reported a close relationship between their attacks and menses, and relief during pregnancy, the cross-sectional associations between migraine and menopause and menopausal complaints were insignificant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
83
2
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(97 citation statements)
references
References 27 publications
8
83
2
4
Order By: Relevance
“…However, with regard to middle-aged women, the relationship between menopause and migraine remains controversial. A few studies have reported that migraine is affected by menopausal status [13,17], whereas others have not found a significant relationship [23,25,26]. We also found that there was no significant difference in migraine prevalence across the three groups.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…However, with regard to middle-aged women, the relationship between menopause and migraine remains controversial. A few studies have reported that migraine is affected by menopausal status [13,17], whereas others have not found a significant relationship [23,25,26]. We also found that there was no significant difference in migraine prevalence across the three groups.…”
Section: Discussionsupporting
confidence: 43%
“…In spite of the high prevalence of middle-aged patients in headache clinics, few studies have been conducted in headache clinics to examine these issues. Furthermore, previous studies have mainly focused on migraine headache [16,17,23]. In contrast, several studies have been conducted in menopausal clinics but without specific differential diagnosis of headaches [3,19,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of sleep, low blood glucose level, dehydration, and stress contribute to the occurrence of migraine attacks (14). Most epidemiological studies demonstrated that pregnant women who experience headaches before pregnancy report to have a 55 -90% improvement in the severity of the attack after they become pregnant (15)(16)(17). A large-scale MIGRA study also revealed a significant decrease in the frequency of migraine during pregnancy (18).…”
Section: Discussionmentioning
confidence: 99%
“…In the same review, the authors identified only three papers addressing perimenopausal symptomatology and the results were not uniform. One study with over 700 patients from a headache clinic showed no clear relationship between migraine and the menopause syndrome 4 . A population-based longitudinal study showed that it was only during the menopausal transition that a clear pattern of migraine and menopausal symptoms could be observed 5 .…”
mentioning
confidence: 99%